(untitled)
The research was carded out at experimental field of Agricultural Research Stadon. Manclor. Joclhpur during April. 2016 to February. 2017 to evaluate the response of pruning time and severity on fmit production. quality and profit.ability of Ber cv. Gola. Six ye..v old grafted U’ees of ber were pnmed al intervals. i.e. on 30 April. 15 May. 30 1’.•1ay, 15 June with two pruning severity levels i.e. 30 per cem and 50 per cent removal of previous season growth. l1le yield impl’oving growlh parameters viz .. comparath•ely Je.ss number of ma.in shoots (21.43 plant’1). maximum number of btanche.s (240.25 planf1). minimum shoOl h::ngth (I 17.60 cm